The role of four life-story aspects in a collaborative decision-making process in the field of leadership development - Loci, Sokol (Economic and business review, 2021)
The aim of this conceptual paper is to add knowledge to the existing leadership development field. We examine the development of core intra- and interpersonal values, specifically the individual collaborative features, by considering life experiences (Day, Fleenor, Atwater, Sturm, & McKee, 2014), and how these personal collaborative features become integrated when leadership members (members of the leadership process) collaborate (Cullen-Lester, Maupin, & Carter, 2017). We formulate the following four relevant propositions: (1) Individual collaborative features should be integrated with the essential features of the leadership members' collaboration during a decision-making process. (2) A life-story aspect has substantive contents and the information drawn from it will therefore shape the leadership members% collaborative features and develop their meaning-making system, while participating in a collaborative decision-making process. (3) The subject under discussion, the context, the actors, and the time of occurrence are the four basic criteria of a life story aspect, in which an event is selected to be placed in. (4) A life story aspect provides fertile grounds for unpacking collaborative tendencies in general and thus implies such tendencies, particularly in the work setting. Consequently, the theoretical contributions of this paper entail advancing and integrating the existing literature of the life-story approach and collaborative decision-making in the leadership development field.
Keywords: decision making; leadership; odločanje; organizacija; organization; vodenje